Climate smart credit scoring for financing of maize value chain smallholder farmers: Sidama Region, Wolayita Zone, Gamo Zone and South Omo - LERSHA; Bioversity International and International Center for Tropical Agriculture; Agricultural Training Institute Ethiopia (2025)
The Climate-Smart Credit Scoring (CSCS) initiative—implemented by Lersha with Alliance Bioversity International–CIAT, ATI, Awash Bank, and key off-takers—aims to expand climate-resilient agricultural finance for 6,000+ maize smallholders in Sidama. The 2025 phase builds on the 2024 pilot by introducing an enhanced scorecard that integrates climate hazard exposure, adaptive capacity, behavioral indicators, and gender-responsive variables to more accurately assess creditworthiness and strengthen farmer inclusion.